2020
DOI: 10.1080/14656566.2020.1746269
|View full text |Cite
|
Sign up to set email alerts
|

Is there a role for dacomitinib, a second-generation irreversible inhibitor of the epidermal-growth factor receptor tyrosine kinase, in advanced non-small cell lung cancer?

Abstract: 2020): Is there a role for dacomitinib, a second-generation irreversible inhibitor of the epidermal-growth factor receptor tyrosine kinase, in advanced non-small cell lung cancer?, Expert Opinion on Pharmacotherapy, ABSTRACT Introduction: Non-small cell lung cancer (NSCLC) is a highly lethal disease. During the past 20 years, the epidermal growth factor receptor (EGFR) has been a relevant target for anticancer drug-design, and a large family of EGFR tyrosine kinase inhibitors (TKI) were designed, which improve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 56 publications
(75 reference statements)
0
12
0
Order By: Relevance
“…51 nM in the central nervous system 28 . Even though the effect of dacomitinib on brain metastases has not been studied in human patients, dacomitinib has displayed brain penetration in preclinical models and thus can be active as well in clinical settings 38,39 . Finally, we intend to increase the practicality of our model by incorporating other resistance mechanisms commonly observed in treated EGFR-m NSCLC and feature other targeted therapies in combination with EGFR inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…51 nM in the central nervous system 28 . Even though the effect of dacomitinib on brain metastases has not been studied in human patients, dacomitinib has displayed brain penetration in preclinical models and thus can be active as well in clinical settings 38,39 . Finally, we intend to increase the practicality of our model by incorporating other resistance mechanisms commonly observed in treated EGFR-m NSCLC and feature other targeted therapies in combination with EGFR inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we changed the therapy to dacomitinib. Among the candidate TKIs, dacomitinib was chosen over afatinib because it has been speculated that dacomitinib might be active in the brain due to its increased brain penetration compared to afatinib ( 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, a preliminary analysis of the first 24 patients has shown that overall response rate (ORR), progression-free survival (PFS), and overall survival (OS) were similar to historical data obtained with the EXTREME regimen [14]. In trials enrolling patients with both metastatic and locoregional disease, dacomitinib, a second-generation irreversible EGFR TKI, led to inconclusive results [15].…”
Section: Egfr Tkismentioning
confidence: 96%